2018
DOI: 10.22146/jpti.23002
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation on Status of Chaetocnema basalis (Coleoptera: Chrysomellidae) as A Vector of Stewart Wilt Disease

Abstract: Chaetocnema pulicaria and C. denticulata are recognized as vectors of Stewart wilt disease caused by Pantoea stewartii on maize. These insects have not been reported yet in Indonesia, but Stewart wilt disease has been reported in Java and Sumatera Islands. Genus Chaetocnema which presented in Indonesia is C.basalis. It is not cleared whether C. basalis is a vector for Stewart wilt disease like C. pulicaria and C. denticulata. This reseach was aimed to conduct the confirmation on status whether C. basalis have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A recent research has also confirmed that 'C. basalis' (= C. nigrica) is a vector of Stewart Wilt disease in Indonesia (Widodo et al, 2017).…”
Section: ) Biologymentioning
confidence: 82%
“…A recent research has also confirmed that 'C. basalis' (= C. nigrica) is a vector of Stewart Wilt disease in Indonesia (Widodo et al, 2017).…”
Section: ) Biologymentioning
confidence: 82%
“…More specifically, it stated that C. pulicaria is the only species important for the long-term survival of bacteria during the winter. In Indonesia, Widodo et al (2017) have even confirmed that insects of the same genus, namely C. basalis fed to maize, were infected with P. stewartii subsp. stewartii is not capable of transmitting the disease to healthy maize plants.…”
Section: Distribution Of P Stewartii Subsp Stewartii To Host Plantsmentioning
confidence: 86%
“…stewartii on corn in West Sumatra also used PCR. Widodo et al (2017) used PCR detection to detect P. stewartii subsp. stewartii in Java and Sumatra, as well as confirming the presence of C. basalis in Indonesia, is not a vector of pathogens.…”
Section: Detection and Identification Of Bacteria P Stewartii Subsp S...mentioning
confidence: 99%